TINGKAT PROFITABILITAS MENU MELALUI METODE MENU ENGINEERING DI SATOO RESTAURANT HW HOTEL PADANG - William Fernando; Lise Asnur (Jurnal Pariwisata Bunda, 2021)
The general purpose of this study was to analyze the level of profitability of the menu at Satoo restaurant and to find out what menu differences are occurring during the Covid-19 pandemic at the Satoo restaurant Hw Hotel through the menu engineering method. The existence of this research is that  it is expected that the hotel can make improvements in making food menu creations that attract consumers, so that Hw Hotel income in the food and beverage section at Satoo restaurant increases. This type of research was descriptive quantitative. Descriptive is used to determine the existence of independent variables. The data analyzed in this study were the level of profitability of the main course and beverage menu at Satoo restaurant. Analysis of the research data used the menu engineering worksheet technique in Microsoft Excel. The results of this study indicate that the main course and beverage menu before the Covid-19 pandemic (January-March 2020) at Satoo Restaurant Hw Hotel Padang which has high profitability are 22 main courses and 12 beverage menus. During the Covid-19 pandemic (September-November 2020) there were 21 main courses and 20 beverage menus that had high profitability. In order for the sales of high-profit menus to increase at Satoo Restaurant Hw Hotel Padang, the management must carry out promotions that attract consumers.